Unveiling the fate and potential neuroprotective role of neural stem/progenitor cells in multiple sclerosis - Hijal, Nora; Fouani, Malak; Awada, Bassel (Frontiers in Neurology, 2024)
Chronic pathological conditions often induce persistent systemic inflammation, contributing to neuroinflammatory diseases like Multiple Sclerosis (MS). MS is known for its autoimmune-mediated damage to myelin, axonal injury, and neuronal loss which drive disability accumulation and disease progression, often manifesting as cognitive impairments. Understanding the involvement of neural stem cells (NSCs) and neural progenitor cells (NPCs) in the remediation of MS through adult neurogenesis (ANG) and gliogenesis—the generation of new neurons and glial cells, respectively is of great importance. Hence, these phenomena, respectively, termed ANG and gliogenesis, involve significant structural and functional changes in neural networks. Thus, the proper integration of these newly generated cells into existing circuits is not only key to understanding the CNS’s development but also its remodeling in adulthood and recovery from diseases such as MS. Understanding how MS influences the fate of NSCs/NPCs and their possible neuroprotective role, provides insights into potential therapeutic interventions to alleviate the impact of MS on cognitive function and disease progression. This review explores MS, its pathogenesis, clinical manifestations, and its association with ANG and gliogenesis. It highlights the impact of altered NSCs and NPCs’ fate during MS and delves into the potential benefits of its modifications. It also evaluates treatment regimens that influence the fate of NSCS/NPCs to counteract the pathology subsequently.